Հայոց ցեղասպանության ժխտողական քաղաքականության արդի դրսևորումները Թուրքիայում - Հովսեփյան, Արմինե (YSU Journal of International Affairs, 2015)
On the eve of the Armenian Genocide centennial Turkey’s government consistently continues its denial policy and makes efforts against recognition and towards suspension of recognition processes of the underlying activities, that are carried out with new approaches and initiatives in both political and academic spheres.This is evidenced when, ahead of the year 2015, Turkey carries out an action plan with segments deepening and strengthening of its recent public diplomacy of usage of some “unfortunate relocation” and “shared pain” thesis, thus, aiming at lowering thepublic tough stand against Turks in Armenian society; carrying out some covert activities with the Diaspora representatives thus creating a gap between Armenia and Diaspora; to counteract and cast a shadow to the Armenian Genocide commemoration activities by carrying out synchronous and mass events; denial of the Armenian Genocide and counteraction to Armenian Diaspora efforts of the Armenian Genocide recognition via activation of Turkish lobby abroad and Azerbaijani propaganda opportunities.
Keywords: Turkey, the Armenian Genocide, denial policy, action plan, Turkish propaganda policy, “forced deportation”, Turkish lobbyist organizations, Turkish-Azerbaijani cooperation, Armenian Diaspora